Late Recurrence of Postdural Puncture Headache. Issue 4 (July 1997) - Sidebotham, David; Willoughby, Ernest; Schug, Stephan A.
Abstract : Background and Objectives: Postdural puncture headache can recur following an epidural blood patch but usually does so within the first week. However, a late recurrence was encountered in a 31-year-old woman with probable lupus vasculitis. Methods: The patient underwent a diagnostic lumbar puncture and suffered a postdural puncture headache. She was treated with an epidural blood patch and had complete resolution of her headache. Five weeks later, she suffered a sudden recurrence of an identical headache and underwent a repeat epidural blood patch. Results: The second headache, like the first, was immediately and completely resolved. Conclusions: A review of risk factors for postdural puncture headache and the role of an epidural blood patch suggests a possible explanation for the late recurrence in this case.